2010
DOI: 10.1016/j.jvs.2010.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Patient-specific biomechanical profiling in abdominal aortic aneurysm development and rupture

Abstract: Major progress has been made in the development of biomechanical profiles for AAA. Large population-based studies for validation of patient-specific biomechanical profiles with rupture risk assessment and tailored decision making are now indicated, particularly with the introduction of AAA screening programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 110 publications
(176 reference statements)
0
32
0
1
Order By: Relevance
“…15,70 DISCUSSION AAA development and rupture are a combined result of the interaction of biological and biomechanical changes, leading to degradation and remodeling of the extracellular matrix. 71 The biomechanical approach offers a new insight into the estimation of AAA rupture risk. 72 Although more complex to obtain, the patient-specific biomechanical profile can more accurately estimate the rupture risk than maximum diameter, morphological indices, and serum markers, 71 as showed by the aforementioned studies.…”
Section: Advances In Aneurysm Computational Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…15,70 DISCUSSION AAA development and rupture are a combined result of the interaction of biological and biomechanical changes, leading to degradation and remodeling of the extracellular matrix. 71 The biomechanical approach offers a new insight into the estimation of AAA rupture risk. 72 Although more complex to obtain, the patient-specific biomechanical profile can more accurately estimate the rupture risk than maximum diameter, morphological indices, and serum markers, 71 as showed by the aforementioned studies.…”
Section: Advances In Aneurysm Computational Modelsmentioning
confidence: 99%
“…Generally, the sites of rupture have been shown to correlate well with regions of high wall stress, underscoring the biomechanical principles of rupture at sites where stress exceeds the local failure strength. 71 Moreover, such sites of elevated PWS have been postulated to be sites of accelerated metabolism since they are associated with high levels of 18F-fluorodeoxyglucose uptake in the aneurysm wall, as detected by positron emission tomographic computed tomography. 72 It has been shown that the simultaneous calculation of an individual's AAA wall strength and conjugation with the PWS in a rupture potential index (RPI) can better differentiate between electively repaired and ruptured AAA cases when compared with either PWS or maximum diameter alone.…”
Section: Advances In Aneurysm Computational Modelsmentioning
confidence: 99%
“…Acknowledging that there are limitations inherent to image acquisition sequences and resolution, deriving accurate segmentation and geometric modeling algorithms are highlighted as open problems in computational vascular biomechanics [7]. Thickness, nonlinear material behavior, strength of the AAA wall, and the spatial distribution of these variables are said to be essential for achieving accurate finite element (FE) simulations and, therefore, also for a realistic prediction of AAA rupture risk [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Patient specific biomechanical profiling has been suggested as a potentially valuable tool in rupture risk assessment [8,9]. Additionally, peak wall stress (PWS) has been reported to be greater in ruptured and symptomatic AAAs compared to asymptomatic AAAs [10], and PWS has been reported to predict location of future rupture [9,11].…”
Section: Introductionmentioning
confidence: 99%